Lung Cancer: Postoperative Imaging and Complications. Issue 5 (September 2017) - de Groot, Patricia M.; Shroff, Girish S.; Carter, Brett W.; Godoy, Myrna C.B.; Plodkowski, Andrew J.; P. Ko, Jane; Munden, Reginald F.
Abstract : In patients with early-stage lung cancer, surgical resection is the treatment of choice. Knowledge of the expected postsurgical changes and awareness of the temporal evolution of these findings as well as potential complications are important in avoiding misinterpretation. We review the surgical techniques used for lung cancer resection, expected postoperative radiologic manifestations, as well as potential early and late postoperative complications in order to improve diagnostic interpretation and optimize patient management.